2020
DOI: 10.1371/journal.pone.0239083
|View full text |Cite
|
Sign up to set email alerts
|

Burden of rare deleterious variants in WNT signaling genes among 511 myelomeningocele patients

Abstract: Genes in the noncanonical WNT signaling pathway controlling planar cell polarity have been linked to the neural tube defect myelomeningocele. We hypothesized that some genes in the WNT signaling network have a higher mutational burden in myelomeningocele subjects than in reference subjects in gnomAD. Exome sequencing data from 511 myelomeningocele subjects was obtained in-house and data from 29,940 ethnically matched subjects was provided by version 2 of the publicly available Genome Aggregation Database. To c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Hence, it is evident that these four genes, namely, NCOA3 , KMT2C , KMT2D , and TNRC6B are interrelated to each other in their function. Also, it has been reported that the TNRC6B gene shows an association with myelomeningocele in the Mexican American population ( Hebert et al, 2020 ). Therefore, these genes might have roles in SB.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, it is evident that these four genes, namely, NCOA3 , KMT2C , KMT2D , and TNRC6B are interrelated to each other in their function. Also, it has been reported that the TNRC6B gene shows an association with myelomeningocele in the Mexican American population ( Hebert et al, 2020 ). Therefore, these genes might have roles in SB.…”
Section: Discussionmentioning
confidence: 98%
“…The correlation between variants pathogenic prediction on protein function or structure and abnormal clinical outcomes are validated by experimental facts at the current stage. For certain phenotypes, an evident enrichment of deleterious variants in a set of disease-related genes, such as the increased mutational burden in essential genes in autism spectrum disorder ( Ji et al, 2016 ), WNT signaling genes in myelomeningocele ( Hebert et al, 2020 ), a set of 5 genes in epilepsy ( Leu et al, 2015 ). The gap between observed higher burden genes and clinical phenotype is then bridged by functional or mechanical experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…They also included all the variants inherited from unaffected healthy parents, potentially explaining their high percentage of variant detection in known candidate genes. Hebert et al (2020) evaluated the burden of rare deleterious variants in WNT signaling genes among 511 MMC patients and showed that 10 WNT signaling genes were disrupted with a higher mutational burden among Mexican American MMC subjects compared to reference subjects. Lemay et al (2015) showed that, by applying WES in 43 trio NTDs families, loss-of-function (LOF)…”
Section: Discussionmentioning
confidence: 99%
“…In order to include a larger cohort of SB cases, we screened our collaborator's SB WES cohort of 511 MMC individuals (Hebert et al, 2020) for the variants in the total of 18 potential candidate genes. However, no likely deleterious variants were identified in these 18 genes.…”
Section: Analysis Of 136 Potential Candidate Genes Identifies Likely ...mentioning
confidence: 99%